2018
DOI: 10.1597/16-148
|View full text |Cite
|
Sign up to set email alerts
|

Content Validity of Patient-Reported Outcome Instruments used with Pediatric Patients with Facial Differences

Abstract: Treatments can change facial appearance and function. This review draws attention to a problem with content validity in existing PRO instruments. Our team is now developing a new PRO instrument called FACE-Q Kids to address this problem.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 46 publications
0
18
0
Order By: Relevance
“…We previously identified the need for PRO instruments developed specifically for CL/P (Klassen et al, 2012). We also showed that existing PRO instruments used with children with facial differences lack content validity (Wickert et al, 2018). Content validity refers to whether content of a PRO instrument is relevant, comprehensive, and comprehensible (Terwee et al, 2018).…”
Section: Introductionmentioning
confidence: 81%
See 1 more Smart Citation
“…We previously identified the need for PRO instruments developed specifically for CL/P (Klassen et al, 2012). We also showed that existing PRO instruments used with children with facial differences lack content validity (Wickert et al, 2018). Content validity refers to whether content of a PRO instrument is relevant, comprehensive, and comprehensible (Terwee et al, 2018).…”
Section: Introductionmentioning
confidence: 81%
“…Tapia et al (2016) also reviewed PRO instruments used in craniofacial research and concluded that there was a need for PRO instruments for pediatric patients with diverse facial differences. An important methodological weakness of existing PRO instruments for patients with facial differences is that they were created without input from patients (Tapia et al, 2016;Wickert et al, 2018). Further, the content of the few PRO instruments designed for patients with facial differences tends to use negative phrasing or content (Wickert et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“… 18 Elsewhere, we report findings from our systematic review of pediatric PRO instruments developed for conditions associated with a facial difference. 8 …”
Section: Methodsmentioning
confidence: 99%
“…In plastic surgery, measurement of the patient’s perspective has been hampered by the lack of validated PRO instruments. Systematic reviews of pediatric PRO instruments for conditions associated with a facial difference identified only 1 ear-specific PRO measure, 1 , 8 , 9 that is, the Congenital Aural Atresia Questionnaire, which measures hearing and psychosocial concerns. 10 Given the lack of ear-specific PRO instruments, researchers have used generic measures.…”
Section: Introductionmentioning
confidence: 99%
“…Beyond the scope of CL/P, few scales exist that measure appraisal of appearance from the patient perspective 10. Congenital anomalies, trauma and other benign and malignant conditions can cause facial or other differences that are stigmatising and may lead to social isolation.…”
Section: Introductionmentioning
confidence: 99%